2009
DOI: 10.1080/13814780903078729
|View full text |Cite
|
Sign up to set email alerts
|

Screening for eating disorders in a psychiatric outpatient population

Abstract: Background: Some studies have found ''hidden'' eating disorders in psychiatric patients. However, eating behaviour, weight, and body image concerns are usually weakly assessed among psychiatric patients. Objectives: a) To analyse the prevalence of eating disorders (ED) in patients referred from primary care for psychiatric assessment; and b) to analyse the psychopathological variables associated with these disorders. Methods. Ninety-three patients underwent psychometric assessment using Derogatis' Symptom Chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Findings that mood and anxiety disorders are common in people with EDs have led clinicians to screen for these disorders in ED populations. Conversely, individuals with MDD/anxiety disorders are rarely screened for EDs or maladaptive eating habits (Jauregui Lobera et al, 2009). If disordered eating is substantially elevated across mood and anxiety disorders, then routine screening for EDs in these populations is also prudent.…”
Section: Introductionmentioning
confidence: 99%
“…Findings that mood and anxiety disorders are common in people with EDs have led clinicians to screen for these disorders in ED populations. Conversely, individuals with MDD/anxiety disorders are rarely screened for EDs or maladaptive eating habits (Jauregui Lobera et al, 2009). If disordered eating is substantially elevated across mood and anxiety disorders, then routine screening for EDs in these populations is also prudent.…”
Section: Introductionmentioning
confidence: 99%
“…The exact prevalence of UFED is unknown, however in a large cohort study of adolescent twins the prevalence of DSM‐5 UFED was found as 4.7% (Wade & O'Shea, 2015). In another study focusing on the psychiatric outpatient population referred from primary care, 3.2% met the criteria for UFED, using the DSM‐IV‐R criteria (Jauregui Lobera et al, 2009) The fact that UFED is among the frequently undetected diagnostic categories might be because of its symptoms being dismissed as insignificant. On the contrary, the evidence suggests that UFED cases are accompanied by significant clinical impairment and morbidity (Mustelin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Primary care settings are among the most common sites patients with EDs first present and many of the patients reported to be undiagnosed (Lebow et al, 2021; Mond et al, 2007). Even fewer cases are recognized when patients present with complaints of other psychiatric disorders, especially anxiety syndromes (Becker et al, 2004; Lobera et al, 2009; Swinbourne & Touyz, 2007). Screening can be a successful method for identifying disordered eating, particularly in complex patients and in psychiatric treatment settings lacking formal assessments (Swinbourne & Touyz, 2007).…”
Section: Introductionmentioning
confidence: 99%